Pattern of and survival following loco-regional and distant recurrence in patients with HPV+ and HPV− oropharyngeal squamous cell carcinoma: A population-based study. (August 2018) - Grønhøj, Christian; Jakobsen, Kathrine Kronberg; Jensen, David H.; Rasmussen, Jacob; Andersen, Elo; Friborg, Jeppe; von Buchwald, Christian
Highlights: HPV-negative patients experienced recurrence more often than HPV-positive patient. Distant recurrence occurred predominantly to the lung, irrespective of HPV-status. HPV-status is an independent and strong predictor of recurrence. Abstract: Objectives: The incidence of human papillomavirus (HPV) positive oropharyngeal squamous cell carcinoma (OPSCC) is increasing. Currently, data is sparse on the pattern and timing of recurrence. This long-term study concerning both HPV- and p16-status aimed to report predictive factors, pattern, timing of loco-regional recurrence (LRR) and distant recurrence (DR), and survival following recurrence in patients diagnosed with OPSCC. Material and methods: We included patients diagnosed with OPSCC from 2000 to 2014 in Eastern Denmark, who were treated with curative intent. Tumors were defined as HPV-positive when they were both HPV-DNA and p16-positive. Time-to-failure and -death were estimated by the Kaplan-Meier method. Cox proportional hazards models were used to evaluate predictors of failure. Results: The cohort consisted of 1244 consecutive patients with OPSCC of which 288 patients (23%) experienced recurrence. Of these patients, the majority (n = 197/1244; 16%) experienced LRR and the remaining (n = 91/1244; 7%) DR. Significantly more HPV-negative patients experienced recurrence (n = 170/486; 35%) compared to HPV-positive patient (n = 112/726; 15%). DR occurred for both groups predominantly to the lung (n = 63/91; 69.2%) followed by the liver and bone. Factors influencing risk of LRR included gender, T-classification, and HPV-status. The same variables influenced risk of DR in addition to the UICC-8 classification, N-classification, pack years of smoking, and performance status. HPV-status was the strongest risk factor for LRR and DR. Conclusion: LRR and DR occur significantly less often in HPV-positive patients compared with HPV-negative patients. HPV-status is an independent and strong predictor of recurrence. DR most commonly occurs to the lungs, irrespective of HPV-status.